1990
DOI: 10.1042/bj2720243
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of insulin secretion from rat islets of Langerhans by interleukin-6. An effect distinct from that of interleukin-1

Abstract: Glucose-induced insulin secretion from islets cultured in the presence of interleukin-6 (IL-6) for 12-24 h was inhibited to a similar extent as when islets were treated with interleukin-1 beta (IL-1 beta). However, unlike IL-1 beta, IL-6 did not potentiate insulin secretion during an acute (30 min) exposure of islets to the cytokine, nor did it inhibit DNA synthesis during a 24 h culture period. A 12 h pretreatment of islets with tumour necrosis factor-alpha (TNF-alpha) combined with IL-1 beta potentiated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0
1

Year Published

1993
1993
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 18 publications
2
36
0
1
Order By: Relevance
“…However, while the relationship between insulin resistance and circulating IL-6 levels is well established, there is little information on an independent association between plasma IL-6 levels and insulin secretion (11). Conflicting results have been also reported from in vitro studies, showing that IL-6 has stimulatory (12)(13)(14), neutral (15), or inhibitory (16,17) effects on insulin secretion from pancreatic ␤-cells, likely as a result of a wide variability in experimental conditions.…”
mentioning
confidence: 63%
“…However, while the relationship between insulin resistance and circulating IL-6 levels is well established, there is little information on an independent association between plasma IL-6 levels and insulin secretion (11). Conflicting results have been also reported from in vitro studies, showing that IL-6 has stimulatory (12)(13)(14), neutral (15), or inhibitory (16,17) effects on insulin secretion from pancreatic ␤-cells, likely as a result of a wide variability in experimental conditions.…”
mentioning
confidence: 63%
“…The limited information previously available on the effects of IL-1b on islet replication, compared to the better known action on b-cell function and death, indicated that IL-1b decreased DNA synthesis in clonal insulinoma cells, 25,26 and in fetal and adult rodent islets. [17][18][19] However, direct assessment of b-cell replication was not performed and it could not be established whether the results reflected effects on islet non-b-cells. Moreover, variable effects were described on fetal islets depending on the duration of exposure to IL-1.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16] The effects of IL-1b on b-cell replication have been less studied, but available data indicate that IL-1b decreased DNA synthesis in fetal 17 and in adult islet cells. [18][19][20] It is basically unknown whether a negative effect of IL-1b on b-cell replication could reduce the capability of b-cells to compensate the increased b-cell loss that takes place in type I diabetes, and contribute to the development of diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…IL-6 has been reported to stimulate the production and release of insulin from cultured rat islet cells (Buschard et al, 1990;Sandler et al, 1990) and from the insulinoma cell line RINm5F (Campbell et al, 1989) and, in addition, produces characteristic degenerative changes in the p cell. However, glucose-stimulated insulin secretion was inhibited when rat islet cells were cultured in the presence of IL-6 (Southern et al, 1990;Sandler et al, 1990). This inhibitory effect of IL-6 was potentiated by IL-lP suggesting that the mechanisms of their effect on insulin release were independent of each other (Southern et al, 1990).…”
Section: Pancreas and Diabetesmentioning
confidence: 95%
“…However, glucose-stimulated insulin secretion was inhibited when rat islet cells were cultured in the presence of IL-6 (Southern et al, 1990;Sandler et al, 1990). This inhibitory effect of IL-6 was potentiated by IL-lP suggesting that the mechanisms of their effect on insulin release were independent of each other (Southern et al, 1990).…”
Section: Pancreas and Diabetesmentioning
confidence: 95%